Multiparametric MRI for Recurrent Prostate Cancer Post Radical Prostatectomy and Postradiation Therapy. (25th May 2014) - Barchetti, Flavio; Panebianco, Valeria
Abstract : The clinical suspicion of local recurrence of prostate cancer (PCa) after radical prostatectomy (RP) and after radiation therapy (RT) is based on the onset of biochemical failure. The aim of this paper was to review the current role of multiparametric-MRI (mp-MRI) in the detection of locoregional recurrence. A systematic literature search using the Medline and Cochrane Library databases was performed from January 1995 up to November 2013. Bibliographies of retrieved and review articles were also examined. Only those articles reporting complete data with clinical relevance for the present review were selected. This review article is divided into two major parts: the first one considers the role of mp-MRI in the detection of PCa local recurrence after RP; the second part provides an insight about the impact of mp-MRI in the depiction of locoregional recurrence after RT (interstitial or external beam). Published data indicate an emerging role for mp-MRI in the detection and localization of locally recurrent PCa both after RP and RT which represents an information of paramount importance to perform focal salvage treatments.